2005
DOI: 10.1179/002029605x70450
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variable scale surface roughness on Si(111): a comparative Brewster angle, ellipsometry and atomic force microscopy investigation

Abstract: To cite this article: M. Lublow & H. J. Lewerenz (2005) Analysis of variable scale surface roughness on Si(111): a comparative Brewster angle, ellipsometry and atomic force microscopy investigation, Transactions of the IMF, 83:5, 238-247 To link to this article: http://dx.Brewster angle analysis (BAA) and single wavelength ellipsometry (SWE) were used to investigate the optical response of Si(111), exposed to subsequent 40% NH 4 F etching steps, each persisting for 20 s. During native oxide layer etchback and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The absorption due to excitation of an electronic defect within the bandgap was expected to change the Brewster angle and the refl ectivity at that angle [136] , which was indeed observed for GaAs and CuInS 2 for instance [137] , thus providing a contactless method for identifi cation of electronic defects at room temperature. In a second application, it was shown that the high surface sensitivity of the method can be used for optical analyses [138,139] . Because the change of the Brewster angle and the refl ectivity at this angle are measured simultaneously, yielding two experimental parameters in one measurement, the method has a certain similarity to ellipsometry where the ellipsometer angles ∆ and Ψ are recorded [140] .…”
Section: In Situ Methods: I B Rewster Angle Analysismentioning
confidence: 99%
“…The absorption due to excitation of an electronic defect within the bandgap was expected to change the Brewster angle and the refl ectivity at that angle [136] , which was indeed observed for GaAs and CuInS 2 for instance [137] , thus providing a contactless method for identifi cation of electronic defects at room temperature. In a second application, it was shown that the high surface sensitivity of the method can be used for optical analyses [138,139] . Because the change of the Brewster angle and the refl ectivity at this angle are measured simultaneously, yielding two experimental parameters in one measurement, the method has a certain similarity to ellipsometry where the ellipsometer angles ∆ and Ψ are recorded [140] .…”
Section: In Situ Methods: I B Rewster Angle Analysismentioning
confidence: 99%
“…The refractive index n ox ¼ ffiffiffiffiffi ffi e ox p of the anodic oxide and its thickness were determined from a fitting procedure of the obtained parabola-shaped curves. The non-zero light beam divergence was corrected by a mathematical procedure [15,16].…”
Section: Methods and Data Evaluationmentioning
confidence: 99%
“…For nanostructures characterization, Brewster-angle analysis (BAA) [11][12][13][14] has recently been applied as a powerful technique for detection of interface roughness and oxide thickness changes in the range 61 Å for the silicon oxide/silicon system [15,16]. In this work, in-situ real-time Brewster-angle reflectometry (BAR) is used for the first time in combination with ex-situ BAA and atomic force microscopy to analyse the interface and oxide structure during current oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The method was also applied in pulsed chemical beam epitaxy (PCBE) to follow epitaxial growth of Ga x I 1Àx P on Si(0 0 1) with below monolayer resolution [5][6][7]. Recently, we performed combined ellipsometry, AFM and BAA analysis of nano-roughness changes induced by etching the native oxide layer on silicon [8]. In the present work, we analyze the silicon/silicon oxide system quantitatively using BAA, AFM and SRPES.…”
Section: Introductionmentioning
confidence: 96%